BioNET-INTERNATIONAL's first consultation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Biosystematics is the study of the relationships and classification of biological diversity. It embraces the construction of classifications, the naming of organisms, and the development of diagnostic methods. Interest in biosystematic services has...